An Evaluation of Grammar Lessons in Selected Moroccan ELT Textbooks - Hassan Ait-Bouzid; Erguig Reddad; Yeou Mohamed (IJELTAL (Indonesian Journal of English Language Teaching and Applied Linguistics), 2019)
This paper is built on the assumption that there are no perfect language teaching textbooks; therefore, it hopes to draw the attention of Moroccan ELT practitioners to the viability of using textbook evaluation to improve the quality of these teaching-learning materials. It aims to investigate ways in which grammar lessons are presented in three Moroccan second year Baccalaureate ELT textbooks currently used in public high schools. It examines the extent to which these lessons help both teachers and students meet the teaching-learning objectives. The study adopts a mixed methods approach and uses content analysis that combines both quantitative and qualitative data analysis techniques. Findings reveal that, although the three textbooks present their grammatical content in different ways, they succeeded in providing challenging grammar contents that suit the needs and interests of the learners. On the other hand, they demonstrate that these textbooks contain problems related to relevance of visual aids, gradation of grammar lessons and authenticity of grammatical examples. Finally, the study concludes with a number of implications that inform future EFL textbook design in Morocco.